A Critical Comprehensive Review of Religiosity and Anxiety Disorders in Adults - Khalaf, Dany R. (Journal of religion and health, 2015)
Over the past three decades, there has been increasing research with respect to the relation of religion and mental health disorders. Consequently, the current article aims to first provide a comprehensive literature review of the interplay between different domains of religiosity and a wide variety of categorical anxiety disorders in adults, and secondly, to uncover the major methodological flaws often yielding mixed, contradictory and unreliable results. The search was conducted using the PubMed/Medline database and included papers published between 1970 and 2012, under a rigorous set of inclusion/exclusion criteria. A total of ten publications were retained as part of the current study, and three main outcomes were identified: (1) certain aspects of religiosity and specific religious interventions have mostly had a protective impact on generalized anxiety disorder (40 % of the studies); (2) other domains of religiosity demonstrated no association with post-traumatic stress disorder (30 % of the studies); and (3) mixed results were seen for panic and phobic disorders.